Experimental study on factors affecting the physical and mechanical properties of shell lime mortar. (20th December 2019) - Zhang, Zhong-jian; Liu, Jian-bin; Li, Biao; Yu, Guo-xin; Li, Li
Highlights: Distribution, production technology, history and usage of shell lime were introduced. Reaction products of shell under different calcination temperatures were analyzed. Sand-lime and water-lime ratios of the best mechanical performance were determined. Effects of adding glutinous rice were studied. Shell lime production has potential in carbon sequestration and environmental protection. Abstract: Shell lime is an building material widely used in ancient buildings in Chinese coastal areas, yet the relationship among the constituents and mechanical properties of shell lime remains poorly understood. This paper aims to study the factors that influence the properties of shell lime mortar. Laboratory tests were conducted on shell lime samples to investigate the properties of shell lime mortar and the influences of the water-lime ratio, sand-lime ratio, curing ages, and the addition of glutinous rice. The results show that the hydraulic component β-CS can be generated in shell lime calcined in the laboratory. The sand-lime and water-lime ratios have major impacts on the disintegration index, shear strength and compressive strength of shell lime mortar, which can also be enhanced by adding glutinous rice.